FAKTA SEJARAH DALAM NOVEL PEREMPUAN KEUMALA KARYA ENDANG MOERDOPO - Wildan Wildan; Mohd. Harun; Yeni Safrida (Center of Language and Cultural Studies, 2015)
This study aims at analyzing historical facts encountered in the novel Keumala Woman (Perempuan Keumala) written by Endang Moerdopo. The analyses comprises of historical facts about: (1) Keumalahayati, (2) historical events, and (3) places having historical story. Data of this study are sequences of events in the novel pertaining to historical realities. New historicism analysis is used to describe the data. The study reveals some findings. First, Keumalahayati is a royal woman who finished her education in Military Academy Makhad Baitul Makdis. Several names that supports historical fact is her husband Sultan Alaiddin Riayat Syah, Cut Limpah, Alfonso, Sultan Muda, Cornelis de Houtman and Frederick de Houtman. Second, historical events incurred in the novel included the development of Makhad Baitul Makdis, the war to Portoguuese in Teluk Haru, rebellion of Sultan Muda, and the arrival of the Dutch for the first time in Aceh. Third, name of places supporting historical facts consisted of Makhad Baitul Makdis, kingdom palace, Krueng Raya Harbor, Pulau Weh, Benteng Inong Balee, Teluk Haru, and Tamiang. This novel is in fact a historical novel particularly that describes the heroism of Keumalahayati.